Cabriology: Putting Digital Collections in the Local Flow at Bruges Public Library - Calis, Koen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Cabrio, the Aquabrowser implementation at the Bruges Public Library, is more than a catalogue makeover. Rich, variable, flashy and truly inspirational, its open structure tackles several strategic issues related to a changing network environment. Digital collections are merged with the catalogue to become part of a hybrid library mediation model. Cabrio focuses on local dynamics and existing participation, which are key features of public libraries, in order to challenge and redefine library perceptions and services.